Ebselen and analogs as inhibitors of Bacillus anthracis thioredoxin reductase and bactericidal antibacterials targeting Bacillus species, Staphylococcus aureus and Mycobacterium tuberculosis - Gustafsson, Tomas N.; Osman, Harer; Werngren, Jim; Hoffner, Sven; Engman, Lars; Holmgren, Arne (Biochimica et biophysica acta, 2016)
Bacillus anthracis is the causative agent of anthrax, a disease associated with a very high mortality rate in its invasive forms. We studied a number of ebselen analogs as inhibitors of B. anthracis thioredoxin reductase and their antibacterial activity on Bacillus subtilis, Staphylococcus aureus, Bacillus cereus and Mycobacterium tuberculosis. The most potent compounds in the series gave IC50 values down to 70nM for the pure enzyme and minimal inhibitory concentrations (MICs) down to 0.4μM (0.12μg/ml) for B. subtilis, 1.5μM (0.64μg/ml) for S. aureus, 2μM (0.86μg/ml) for B. cereus and 10μg/ml for M. tuberculosis. Minimal bactericidal concentrations (MBCs) were found at 1–1.5 times the MIC, indicating a general, class-dependent, bactericidal mode of action. The combined bacteriological and enzymological data were used to construct a preliminary structure–activity-relationship for the benzoisoselenazol class of compounds. When S. aureus and B. subtilis were exposed to ebselen, we were unable to isolate resistant mutants on both solid and in liquid medium suggesting a high resistance barrier. These results suggest that ebselen and analogs thereof could be developed into a novel antibiotic class, useful for the treatment of infections caused by B. anthracis, S. aureus, M. tuberculosis and other clinically important bacteria. Furthermore, the high barrier against resistance development is encouraging for further drug development. We have characterized the thioredoxin system from B. anthracis as a novel drug target and ebselen and analogs thereof as a potential new class of antibiotics targeting several important human pathogens. •Ebselen and derivatives are potent inhibitors of B. anthracis thioredoxin reductase.•The compounds are potent antibacterials with a bactericidal mode of action.•The spectrum of activity includes Bacillus spp, S. aureus and M. tuberculosis.•The barrier for resistance development is high.